Anesthetic Management for Percutaneous Minimally Invasive Fetoscopic Surgery of Spina Bifida Aperta: A Retrospective, Descriptive Report of Clinical Experience. Issue 1 (March 2018) - Arens, C.; Koch, C.; Veit, M.; Greenberg, R.S.; Lichtenstern, C.; Weigand, M.A.; Khaleeva, A.; Schuerg, R.; Kohl, T.
Abstract : ( Anesth Analg . 2017;125(1):219-222) Liberal administration of tocolytic drugs (e.g. indomethacin) and intravenous fluids along with high concentrations of volatile anesthetic gases during fetal surgery are thought to contribute to the development of maternal pulmonary edema. Consequently, during the introduction of the Minimally Invasive Fetoscopic Approach (MIFA) for the closure of fetal spina bifida aperta (SBA), Hering and Kohl identified a general anesthetic technique that reduced concentrations of volatile anesthetic and thus minimized adverse side effects of deep anesthesia (hemodynamic depression, pulmonary edema, and need for vasopressor support). In this retrospective case series, the authors described their own clinical experiences with a modified Hering-Kohl-Protocol in patients undergoing MIFA for SBA. In this modified protocol, vasopressor management is guided by pulse contour analysis (PiCCO) alone and atosiban is the first-line agent for perioperative tocolysis instead of indomethacin.